Entrepreneurship and innovation towards rural development evidence from a peripheral area in Portugal - Pato, Lúcia (2021)
Based on an exploratory research, this study highlights the role of pure rural entrepreneurship towards rural development of an inland and mountainous area of Portugal—Montemuro. Thanks to the Institute of Cultural Affairs and the energy of the rural communities, some people of the rural area have been stimulated thirty years ago to develop endogenous, entrepreneurial and innovative initiatives in the countryside. The benefits of all these rural entrepreneurial and endogenous initiatives are visible nowadays. Some villages of the rural area have more people, socio-economic dynamics were revitalize and some job opportunities were created. Therefore, in a context of depopulation and crisis of peripheral and interior areas, our study demonstrates that rural entrepreneurship and innovation based on endogenous resources are key for the welfare of the rural society.